Sex crimes, honour, and the law in early modern Spain : Vizcaya, 1528-1735 - Barahona, Renato, 1944- (University of Toronto Press, 2003)
Renato Barahona has distilled years of meticulous research into a pioneering study of sexual criminality, women, honour and the law in early modern Basque Spain. Presenting his argument in a lucid and engaging style, Barahona explores the litigation of honour and dishonour by female victims of seduction. He successfully demonstrates that - in this region and era - female honour lost through sexual transgression could be redeemed through recourse to the law. Drawing from records of over 350 lawsuits, which took place between 1500 and 1750 (all primary sources, and all previously unpublished), Barahona offers new insights into the role of the secular courts in serving the interests of women. He does much to broaden our understanding of courtship, sexual practices, sexual vocabulary, marriage customs, cohabitation and violence against women. Sex Crimes, Honour, and the Law in Early Modern Spain will be welcomed by students and scholars in the areas of social history, women's studies, law and literature.